Industrial Research - United Nations Industrial Development Organization, Vienna; Sharpston, Charles (New York: United Nations, 1969)
The present series of monographs deal with specific industrial sectors; some with matters of general industrial policy; and others with various aspects of international economic co-operation. While the various economic, technological and institutional aspects of the subject matter are treated within the context of the conditions generally prevailing in the developing countries.
Based on the proceedings of the International Symposium on Industrial Development (Athens, November-December 1967)
''United Nations Publication sales no.: E.69.II.B.39, vol. 12''
Includes bibliographical references.
ne 13/03/2018
Loan
Keywords: Industrialization; Developing countries